Adenoid cystic carcinoma of the hard palate presenting as ipsilateral sixth nerve palsy - Nair, Akshay Gopinathan (Indian J Ophthalmol, 2018)
Adenoid cystic carcinoma (ACC) is an uncommon malignant neoplasm composed of basaloid epithelial and myoepithelial cells. The palate is the most commonly involved intraoral site for ACC. Here, we document the case of an advanced ACC arising from the hard palate that presented with right-sided sixth nerve palsy in a 75-year-old male with no other systemic illnesses. ACC of the head and neck involving the cavernous sinus and presenting as isolated sixth nerve palsy is exceedingly rare. In the absence of vasculopathic or ischemic risk factors, regardless of the age of the patient; neuroimaging should be performed in cases of isolated nontraumatic sixth nerve palsy.